Penyuluhan Kebiasaan Mencuci Tangan yang Baik dan Benar pada siswa PAUD Pelita Hati Desa Pematang Balam Bengkulu Utara - Sari, Fadillah; Parwito, Parwito; Susilo, Edi; Salamun, Salamun; Hermawati, Dwi; Ikhsan , Ikhsan (JURNAL BESEMAH, 2022)
The purpose of this community service program is to improve the ability to wash hands properly and correctly using soap, increase student motivation in washing hands, improve student hand washing habits. This community service program is carried out at Pelita Hati PAUD. The results of this community service program run smoothly, conducive and according to procedures. Pelita Hati PAUD students were very enthusiastic and seemed to be able to wash their hands properly.